Colloid Cyst of the Third Ventricle: Imaging-pathologic Correlation - Armao, Diane; Castillo, Mauricio; Chen, Hong; Kwock, Lester (American Journal of Neuroradiology, 2000)
Summary: Colloid cysts are relatively rare intracranial lesions located in the rostral aspect of the third ventricle. They may produce acute hydrocephalus, brain herniation, and lead to death. Although the clinical and imaging features of colloid cysts are well known, their etiology and the factors responsible for their imaging features continue to be a subject of debate. We present the imaging-pathologic correlation of a patient with a colloid cyst as well as data supporting the fact that the presence of cholesterol is probably responsible for the MR imaging features exhibited by some colloid cysts.